Судноплавство як фактор забруднення морського середовища. - Звягінцева, Д.С.; Звягинцева, Д.С.; Zvjaginceva, D (My University, 2011)
In this article negative displays of the navigation that harm to marine environment are analyzed. The positions of the scientists to this problem are researched. The classiﬁ cation of negative inﬂ uences on marine environment from navigation is offered. The attempt of differentiating of negative conse- quences from technical exploitation of the vessels and from the use of the vessels on their functional purpose is done.
Звягінцева Д.С. Судноплавство як фактор забруднення морського середовища. / Д.С. Звягінцева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 12-18 . С.110 - 116.
Keywords: Судноплавство; Забруднення морського середовиша; Класифікація негативного вплива судноплавства на морське середовище.; Шкода морському середовищу; Вред морской среде; Класификация негативного влияния судоходства на морскую среду; Загрязнение морской среды; Судоходство; shipping; Marine pollution; Classification of the negative impact of shipping on the marine environment; The harm to the marine environment